A phosphotyrosine displacement mechanism for activation of Src by PTPα - Zheng, Xin-Min (Oxford University Press, 2000)
Protein tyrosine phosphatase α (PTPα) is believed to dephosphorylate physiologically the Src proto-oncogene at phosphotyrosine (pTyr)527, a critical negative-regulatory residue. It thereby activates Src, and PTPα overexpression neoplastically transforms NIH 3T3 cells. pTyr789 in PTPα is constitutively phosphorylated and binds Grb2, an interaction that may inhibit PTPα activity. We show here that this phosphorylation also specifically enables PTPα to dephosphorylate pTyr527. Tyr789→Phe mutation abrogates PTPα–Src binding, dephosphorylation of pTyr527 (although not of other substrates), and neoplastic transformation by overexpressed PTPα in vivo. We suggest that pTyr789 enables pTyr527 dephosphorylation by a pilot binding with the Src SH2 domain that displaces the intramolecular pTyr527–SH2 binding. Consistent with model predictions, we find that excess SH2 domains can disrupt PTPα–Src binding and can block PTPα-mediated dephosphorylation and activation in proportion to their affinity for pTyr789. Moreover, we show that, as predicted by the model, catalytically defective PTPα has reduced Src binding in vivo. The displacement mechanism provides another potential control point for physiological regulation of Src-family signal transduction pathways.